ISOLASI DAN PENETAPAN KADAR SENYAWA ANTIFUNGAL p-Methoxybenzylidene p-aminophenol DARI AKAR Acacia mangium - Nur Hidayati (Jurnal Pemuliaan Tanaman Hutan, 2012)
Acacia mangium has been planted on large scale of industrial forest plantation in Indonesia, especially in Sumatera and Kalimantan islands. It has been reported that large area of mangium plantations have been infected rot root disease caused by Ganoderma sp. To date, there was no information of mangium which resist to Ganoderma sp. The study had by carried out with two aims : (1) isolate a compound with antifungal properties, the antifungal was identified as  p-Methoxybenzylidene p-aminophenol in the category of phenolic compounds. from the roots of healthy mangium, and (2) determine the concentration of antifungal compound from roots of healthy mangium. The roots of healthy mangium from the first generation seedling seed orchard in Wonogiri, Central Java, were used. Mangium roots which had had their external and internal parts separated were  macerated in a solvent of nhexane and methanol. Methods of the isolation of the antifungal compound were thin-layer chromatography (TLC), column chromatography and thin layer preparative chromatography. The antifungal was identified as p-Methoxybenzylidene p-aminophenol in the category of phenolic compounds. Determination of the concentration of the antifungal compound was done by a TLC densitometer on six different families of trees. The results revealed that the antifungal compound was successfully isolated in its from methanol extract from the interior of the root. Results of identification with the TLC densitometer method showed that among the six  families of trees, number 44 had the highest concentration at 40,52% w/w and number 67 showed the lowest concentration at 19,88% w/w.